2013
DOI: 10.3190/jgeosci.147
|View full text |Cite
|
Sign up to set email alerts
|

Platinum-group elements (PGE) and their principal carriers in metal-rich black shales: an overview with a new data from Mo-Ni-PGE black shales (Zunyi region, Guizhou Province, south China)

Abstract: Lower Cambrian Mo-Ni sulfidic black shales from the Huangjiawan mine (Guizhou Province, south China) have anomalous platinum-group elements (PGE) concentrations (up to ˜1 ppm in total). In order to identify principal PGE carriers, we used heavy mineral separates which were produced by innovative hydroseparation techniques. Subsequent detailed mineralogical study using electron microprobe did not result in the identification of discrete platinum-group minerals. Pyrite (grainy, not framboidal), millerite and ger… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Examples are (1) manganese nodules and crusts formed in the marine environment on the ocean floor (e.g. Balaram et al , 2006; Banakar et al , 2007); (2) Mo–Ni–PGE black shale ores of China (Mao et al , 2002; Pašava et al , 2013) thought to have formed from evaporating sea water; (3) secondary oxide ores produced by weathering of primary mineralization (e.g. Great Dyke; Locmelis et al , 2010; Oberthür et al , 2013); and (4) placers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Examples are (1) manganese nodules and crusts formed in the marine environment on the ocean floor (e.g. Balaram et al , 2006; Banakar et al , 2007); (2) Mo–Ni–PGE black shale ores of China (Mao et al , 2002; Pašava et al , 2013) thought to have formed from evaporating sea water; (3) secondary oxide ores produced by weathering of primary mineralization (e.g. Great Dyke; Locmelis et al , 2010; Oberthür et al , 2013); and (4) placers (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, if we consider other mineral occurrences that do not have a direct connection with magmatism, the picture will be somewhat different. For example, for the mineralisation of Mo-Ni-PGE in black shales [5], the distribution coefficients of invisible forms of Pt and Pd between pyrite and gersdorffite (NiAsS), which is the Ni-analogue of arsenopyrite, on average amount to~0.9; that is, no significant fractionation of these elements in the sulpharsenide phase is detected. On the other hand, Kravtsova et al [21] suggested that the increased content of PGEs and Au are typical of arsenopyrites formed at the hydrothermal stage, at the deposit of metamorphogenic-hydrothermal genesis, as confirmed by the rather high content of the structural forms of Pt and Pd in arsenopyrite.…”
Section: Previous Studies and Problem Statementmentioning
confidence: 99%
“…Among the deposits of particular interest are unconventional (amagmatic) enrichments in sedimentary rocks such as black shale (e.g. Pašava et al, 2013;Wilde et al, 2003) and in carbonaceous and calcareous metasedimentary rocks, all of which are Paleozoic and Precambrian (e.g. Sener et al, 2002;Wilde et al, 2003).…”
Section: Geological Origin Of Platinum In Placer Depositsmentioning
confidence: 99%